2009
DOI: 10.1027/1614-0001.30.4.201
|View full text |Cite
|
Sign up to set email alerts
|

On the Social Malleability of Traits

Abstract: The current study investigated the effects of social context on Big 5 trait expression, and the moderating influence of social context on gender differences in personality. A short Big 5 instrument assessed trait expression in three contexts: with parents, with friends, and with work colleagues. Findings indicated significant cross-context variation in all five traits, while also showing cross-context within-trait correlations. These cross-context correlations found that Conscientiousness was the most stable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The Big Five personality traits characterize personality across five dimensions: openness (open to change and new experiences, imaginative, insightful), conscientiousness (reliable, hardworking, trustworthy, dependable, orderly, thorough), extraversion (sociable, talkative, impulsive, energetic, and assertive behaviors), agreeableness (cooperative, helpful, likeable, sympathetic, kind), and neuroticism (anxiety, personal insecurity, tension, hostility, irritability; Gosling et al, 2003;McCrae & John, 1992). The five personality traits may change throughout life over a long time scale and in response to life events (Specht et al, 2011) although expression of personality traits may depend on social context (Robinson, 2009). The Big Five dimensions are known to correlate with a variety of desirable academic outcomes (Lounsbury et al, 2004;Trapmann et al, 2007).…”
Section: Big Five Personalitymentioning
confidence: 99%
“…The Big Five personality traits characterize personality across five dimensions: openness (open to change and new experiences, imaginative, insightful), conscientiousness (reliable, hardworking, trustworthy, dependable, orderly, thorough), extraversion (sociable, talkative, impulsive, energetic, and assertive behaviors), agreeableness (cooperative, helpful, likeable, sympathetic, kind), and neuroticism (anxiety, personal insecurity, tension, hostility, irritability; Gosling et al, 2003;McCrae & John, 1992). The five personality traits may change throughout life over a long time scale and in response to life events (Specht et al, 2011) although expression of personality traits may depend on social context (Robinson, 2009). The Big Five dimensions are known to correlate with a variety of desirable academic outcomes (Lounsbury et al, 2004;Trapmann et al, 2007).…”
Section: Big Five Personalitymentioning
confidence: 99%
“…In contrast to Wittmann's (1988) classical full asymmetry, we should not necessarily expect a zero correlation as contextualized personality items tend to be correlated across contexts: Individuals often show cross-contextual consistency in their behaviors. For example, Robinson (2009) showed that Extraversion scores that were contextualized to interactions with friends, with parents, and with work colleagues correlated in the range of .18 to .41.…”
Section: From Hidden Framings To Hidden (A)symmetriesmentioning
confidence: 99%
“…Agreeableness, which like extraversion contains important social aspects, was not significantly related to variety in daily social partners. It is possible that extraversion, which has a positive affective signature in addition to a social one, is more contextually malleable and more responsive to situational aspects than agreeableness (Robinson, 2009). On the other hand, the results suggest that people express agreeableness regardless of a broad or limited range of daily social interaction partners.…”
Section: Discussionmentioning
confidence: 99%
“…Borrowing from the trait literature, individuals report different levels in personality traits when they are with different people (e.g., with parents or friends; Robinson, 2009; Sheldon et al, 1997). A study in the workplace found that employees varied in their state expression when they were among different people: Employees displayed lower extraversion, agreeableness, and conscientiousness when interacting with their supervisor or peers than when interacting with customers (Huang & Ryan, 2011).…”
Section: Introductionmentioning
confidence: 99%